Morocco : the Islamist awakening and other challenges - Howe, Marvine (OUP E-Books., 2005)
In Morocco, Marvine Howe, a former correspondent for The New York Times presents an incisive and comprehensive review of the Moroccan kingdom and its people, past and present. She provides a vivid and frank portrait of late King Hassan, whom she knew personally and credits with laying the foundations of a modern, pro-Western state and analyzes the pressures his successor, King Mohammed VI has come under to transform the autocratic monarchy into a full-fledged democracy. Howe addresses emerging issues and problems--equal rights for women, elimination of corruption and correction ofglaringeconomic and social disparities--and asks the fundamental question: can this ancient Muslim kingdom embrace western democracy in an era of deepening divisions between the Islamic world and the West?